2011
DOI: 10.1002/jcu.20883
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between transvaginal sonography after diagnostic hysteroscopy and laparoscopic chromopertubation for the assessment of tubal patency in infertile women

Abstract: TVS performed directly after diagnostic hysteroscopy in infertile patients provides additional nformation regarding tubal patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…In 36 of these cases, unilateral or bilateral tubal patency was confirmed by DL. In 17 of the remaining 19 case .In contrary to the reported finding (19) In contrary to the reported finding ; Bulletti CB investigated the exclusion of pelvic factor of infertility through the same tests, namely SHSG, HSG and laparoscopy In their study endometriosis was diagnosed laparoscopically in 344 out of 1080women. Only 44 women (13%) with endometriosis showed bilateral tubal block (20) 68 infertile patients underwent hysterosonosalpingography using saline as contrast medium, and then further assessment by laparoscopy and hysteroscopy were performed to them Sensitivity and specificity of hysterosonosalpingography for the assessment of tubal patency was 100% and66% respectively.…”
Section: Discussion:-mentioning
confidence: 78%
“…In 36 of these cases, unilateral or bilateral tubal patency was confirmed by DL. In 17 of the remaining 19 case .In contrary to the reported finding (19) In contrary to the reported finding ; Bulletti CB investigated the exclusion of pelvic factor of infertility through the same tests, namely SHSG, HSG and laparoscopy In their study endometriosis was diagnosed laparoscopically in 344 out of 1080women. Only 44 women (13%) with endometriosis showed bilateral tubal block (20) 68 infertile patients underwent hysterosonosalpingography using saline as contrast medium, and then further assessment by laparoscopy and hysteroscopy were performed to them Sensitivity and specificity of hysterosonosalpingography for the assessment of tubal patency was 100% and66% respectively.…”
Section: Discussion:-mentioning
confidence: 78%
“…HYS is the gold standard method for evaluation of intracavitary lesions; nevertheless, HYS is not a method to investigate TP (9). Several studies suggested that HYS could be used in evaluation of TP if combined with USG (5,17). In this method, the tube is considered patent when the turbulence of the contrast is visualized on the side or in the Douglas pouch.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy (LPS) provides both a panoramic view of the pelvic reproductive anatomy and a magnified view of the uterine, ovarian, tubal, and peritoneal surfaces. Laparoscopic chromopertubation (LCT) (introducing methylene blue into the uterine cavity being injected through the cervical canal by a cannula during the procedure and then observation as it comes out of the ends of the tubes into the peritoneal cavity) is considered to be the gold standard for TP (5). However, LPS is an invasive surgical procedure, requires general anesthesia, provides no information regarding the uterine cavity and involves the usual risks of surgery (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During hysteroscopy, the uterine cavity is viewed at a 30-degree angle, which allows for visualization of both mouths of the fallopian tube, fundus, anterior and posterior wall of the uterus as well as the lateral sides of the uterine cavity (10). At the height of the internal uterine mouth with the hysteroscope, a panoramic image of the uterine cavity is displayed, and the presence of any pathological findings, such as endometrial polyps (which are often observed), submucosal fibroids, septa, and adhesions, can be easily visualized.…”
Section: Methodsmentioning
confidence: 99%